Compositional transformation of Ni2+ and Fe0 during the removal of Ni2+ by nanoscale zero-valent iron and the implications to groundwater remediation - Anang, Emmanuella (Water science and technology : a journal of the International Association on Water Pollution Research, 2023)
The use of nanoscale zero-valent iron (nZVI) to remove heavy metal ions like Ni2+ from groundwater has been extensively studied; however, the compositional transformation of the Ni2+ and Fe0 during the removal is not clearly comprehensible. This study provides an insight into the componential, structural, and morphological transformations of Ni2+ and Fe0 at a solid-liquid interface using various characterization devices. The underlying mechanism of transformation was investigated along with the toxicity/impact of the transformed products on the groundwater ecosystem. The results indicated that Fe0 is transformed into lath-like lepidocrocite (γ-FeOOH), twin-crystal goethite (α-FeOOH), and spherical magnetite (Fe3O4), while Ni2+ is converted into Fe0.7Ni0.3 alloy and Fe-Ni composite (trevorite - NiFe2O4) with a fold-fan morphology. The Fe0 transformation mechanism includes the redox of Fe0 with Ni2+, H2O, and dissolved oxygen, the combination of Fe2+ and OH- produced by Fe0 corrosion to amorphous ferrihydrite, and the further mineralogical transformation to Fe oxides with the aid of Fe2+ adsorbed on ferrihydrite. The conversion of Ni2+ is accomplished by reduction by Fe0 and surface coordination with Fe oxides. Compared with Ni2+ and Fe0, the toxicity and bioavailability of the transformed products are significantly reduced, hence conducive to the application of zero-valent iron technology in groundwater remediation